Novel 2‐cyanoacrylamido‐4, 5, 6, 7‐tetrahydrobenzo[b]thiophene derivatives as potent anticancer agents. Issue 10 (13th July 2020) - Sroor, Farid M.; Aboelenin, Mohamad M.; Mahrous, Karima F.; Mahmoud, Khaled; Elwahy, Ahmed H. M.; Abdelhamid, Ismail A.
Abstract: Ethyl 2‐acrylamido‐4, 5, 6, 7‐tetrahydrobenzo[ b ]thiophene‐3‐carboxylate as well as its corresponding bis ‐derivatives, 5 –10, with aliphatic linkers were synthesized, fully characterized, and tested as novel anticancer agents. The targeted compounds, 5 –10, were obtained by the Knoevenagel condensation reactions of bis ‐ o ‐ or ‐ p ‐aldehyde with a molar ratio of ethyl 2‐(2‐cyanoacetamido)‐4, 5, 6, 7‐tetrahydrobenzo[ b ]thiophene‐3‐carboxylate of 2 in the presence of piperidine in excellent yields (93–98%). The in vitro anticancer activities of the prepared compounds were evaluated against HepG2, MCF‐7, HCT‐116, and BJ1 cells. Compounds 7 and 9 emerged as the most promising compounds, with IC50 values of 13.5 and 32.2 µg/ml, respectively, against HepG2 cells, compared with the reference drug doxorubicin (IC50 : 21.6 µg/ml). Real‐time reverse‐transcription polymerase chain reaction was used to measure the changes in expression levels of the COL10A1 and COL11A1, ESR1, and ERBB2, or AXIN1 and CDKN2A genes within the treated cells, as genetic markers for colon, breast, or liver cancers, respectively. Treatment of the colon cancer cells with compounds 5, 9, and 10, or breast and liver cancers cells with compounds 7, 8, 9, and 10 downregulated the expression of the investigated tumor markers. The DNA damage values (depending on comet and DNA fragmentation assays) increased significantly upon treatment of colon cancer cells with compounds 5, 9, and 10, and breast and liver cells with compounds 8, 9, and 10 . The structure–activity relationship suggested that the increase of the chain of the alkyl linker increases the anticancer activity and the compounds with bis ‐cyanoacrylamide moieties are more active than those with one cyanoacrylamide moiety. Abstract : Bis ‐ethyl 2‐(2‐cyanoacrylamido)‐4, 5, 6, 7‐tetrahydrobenzo[ b ]thiophene‐3‐carboxylate derivatives 5 –10 with aliphatic linkers were synthesized and tested in vitro as anticancer agents against HepG2, MCF‐7, HCT‐116, and BJ1 cells. Compounds 7 and 9 emerged as the most promising compounds, with IC50 values (HepG2) of 13.5 and 32.2 µg/ml, respectively, compared with doxorubicin. The effects of compounds 7 and 9 on gene expression and DNA fragmentation were evaluated.